Karst ecosystem services and their roles in the management of Gunung Sewu UNESCO global geopark - Hilary Reinhart; Rakhmat Dwi Putra; Muhamad Rifki Rafida (Center for Science and Technology, IAIN Surakarta, 2023)
As a member of the Global Geopark Network, Gunung Sewu UNESCO Global Geopark is designed to attract tourists, with a focus on the tourism industry to generate revenue. However, this development triggers environmental pressure on the already fragile karstic ecosystem, necessitating the implementation of mitigation measures. This research aims to employ Karst Ecosystem Services (KESs) as a tool for managing the karst area and the Geopark itself, exploring both the concept and its implementation. Two examples of ecosystem services, scenic and habitat quality, are generated using InVEST tools as the representations of Karst Ecosystem Services. In the Karst of Gunung Sewu, the habitat quality of tree covers, ponds, and caves is threatened by limestone mining, agriculture, and large-scale infrastructure, while the scenic quality is degraded by the presence of construction sites, large statues, and unused or abandoned building. These ecosystem services can contribute to strengthening the Geopark’s pillars through conserving intactness and maintaining energy flow within the habitat for the Geoconservation pillar. For geoeduaction pillar, scenic landscapes provide visual interpretation, and the integrity of landforms supports morphological interpretation. Lastly, habitat and scenic quality can be developed to enhance tourism attraction while maintaining the environment quality for the Sustainable Local Economic Development pillar.